Identification of covalent inhibitors that disrupt M. tuberculosis growth by targeting multiple serine hydrolases involved in lipid metabolism - Babin, Brett M.; Keller, Laura J.; Pinto, Yishay; Li, Veronica L.; Eneim, Andrew S.; Vance, Summer E.; Terrell, Stephanie M.; Bhatt, Ami S.; Long, Jonathan Z.; Bogyo, Matthew (Cell chemical biology, 2022)
The increasing incidence of antibiotic-resistant Mycobacterium tuberculosis infections is a global health threat necessitating the development of new antibiotics. Serine hydrolases (SHs) are a promising class of targets because of their importance for the synthesis of the mycobacterial cell envelope. We screen a library of small molecules containing serine-reactive electrophiles and identify narrow-spectrum inhibitors of M. tuberculosis growth. Using these lead molecules, we perform competitive activity-based protein profiling and identify multiple SH targets, including enzymes with uncharacterized functions. Lipidomic analyses of compound-treated cultures reveal an accumulation of free lipids and a substantial decrease in lipooligosaccharides, linking SH inhibition to defects in cell envelope biogenesis. Mutant analysis reveals a path to resistance via the synthesis of mycocerates, but not through mutations to SH targets. Our results suggest that simultaneous inhibition of multiple SH enzymes is likely to be an effective therapeutic strategy for the treatment of M. tuberculosis infections. [Display omitted] •JCP276 is a narrow-spectrum inhibitor of Mycobacterium tuberculosis growth•Phthiocerol dimycocerate confers resistance to JCP276•JCP276 inhibits multiple nonessential serine hydrolases•Serine hydrolase inhibitors lead to an accumulation of free fatty acids The increasing incidence of drug-resistant Mycobacterium tuberculosis necessitates the discovery of new therapeutics and therapeutic targets. Babin et al. use a phenotypic screen to identify a potent covalent inhibitor of M. tuberculosis growth that targets serine hydrolases and disrupts lipid metabolism.